PENGARUH WEBSITE SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMA NEGERI 1 BOJONEGARA PADA SUBKONSEP SISTEM HORMON MANUSIA - Farida Restulowati; Mila Ermila Henriyan; Siti Gia Syauqiyah Fitri (Universitas Sultan Ageng Tirtayasa, 2016)
ABSTRACTThis study was aimed to investigate the effect of a website as a media toward students’ learning outcomes at XI grade of SMAN 1 Bojonegara on the subconcept of human hormone system. Class XI IPA 1 as the experimental group and the class XI IPA 2 as the control group. The samples were choosen by simple random sampling technique. The method used was a quasi experimental design with Randomized Control Group Eksperimental. Data were collected by using objective tests and questionnaires. The calculated t test with 95% confidence (α = 0,05) suggest that student ability of the experimental group was better than control group. Students’ response to the use of website as learning media was good. It can be concluded that website as learning media had an effect towards students’ learning outcomes in the subconcepts of human hormone system.